2017
DOI: 10.1007/s15010-016-0976-x
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis and liver transplantation in patients co-infected with HIV and hepatitis B or C: an observational cohort study

Abstract: This study assessed the likelihood of referral for liver transplantation assessment in a prospective cohort of patients co-infected with HIV and hepatitis B or C with complications of cirrhosis. There were 141 co-infected patients from 11 UK centres with at least one complication of cirrhosis recorded (either decompensation or hepatocellular carcinoma) out of 772 identified with cirrhosis and/or HCC. Only 23 of these 141 (16.3%) were referred for liver transplantation assessment, even though referral is recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…HIV infection complicated by HCV or HBV coinfection seems to greatly precipitate in the development of HCC due to accelerated carcinogenicity, although the real pathogenic mechanism has not been fully understood [ 41 , 42 , 43 , 44 , 45 ]. Currently, it has been clearly shown that 25% of liver death in HIV+ patients is linked to the presence of HCC [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection complicated by HCV or HBV coinfection seems to greatly precipitate in the development of HCC due to accelerated carcinogenicity, although the real pathogenic mechanism has not been fully understood [ 41 , 42 , 43 , 44 , 45 ]. Currently, it has been clearly shown that 25% of liver death in HIV+ patients is linked to the presence of HCC [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between alcohol abuse and antiretroviral therapy‐related toxicity, hepatitis C virus (HCV) co‐infection has been so far the major underlying cause, with a reported prevalence of 70%. 1 , 2 , 3 Liver transplantation (LT) has been demonstrated to be a feasible and effective treatment for ESLD HIV‐positive patients, even in the presence of hepatocellular carcinoma (HCC) diagnosis, reaching outcomes comparable to non‐HIV patients. 1 , 2 , 3 Nonetheless, HCV/HIV co‐infected LT recipients have been characterized by a dismal outcome, mainly due to a severe HCV recurrence on the liver allograft, that is accelerated by HIV co‐infection.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 Liver transplantation (LT) has been demonstrated to be a feasible and effective treatment for ESLD HIV‐positive patients, even in the presence of hepatocellular carcinoma (HCC) diagnosis, reaching outcomes comparable to non‐HIV patients. 1 , 2 , 3 Nonetheless, HCV/HIV co‐infected LT recipients have been characterized by a dismal outcome, mainly due to a severe HCV recurrence on the liver allograft, that is accelerated by HIV co‐infection. 4 Nowadays, direct‐acting anti‐HCV drugs (DAAs) have been effectively controlling such risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subgroup that deserves to be highlighted is patients coinfected with hepatitis B or C. These patients have higher risks of cirrhosis progression, HCC and terminal hepatic disease than the monoinfected (9) . Historically, the coinfected patients with hepatitis C had a worse prognosis because the immunosuppression frequently resulted in infectious complications and aggressive recurrence of the virus C, which is the leading cause of death in these patients.…”
Section: Discussionmentioning
confidence: 99%